More Attractive or More Interactive? The Effects of Multi-Leveled Emotional Design on Middle School Students’ Multimedia Learning - Shangguan, Chenyu; Wang, Zhen; Gong, Shaoying; Guo, Yawei; Xu, Sheng (Frontiers in Psychology, 2020)
Previous studies on multimedia learning have provided shreds of evidence for the positive effect of visually attractive emotional design on college students' emotion and learning outcomes. However, the effect may vary among middle school students. The aim of this study was to examine the impacts of visual and behavioral emotional design on the emotional, motivational and cognitive outcomes of middle school students. In Experiment 1, 50 participants (ages 13-15) were randomly assigned to one of two conditions: visual positive emotional design (colorful and anthropomorphic design) and visual neutral emotional design (achromatic and without anthropomorphic design). In Experiment 2, 173 participants (ages 13-16) were randomly assigned to one of four conditions created by the two factors: visual emotional design (positive vs. neutral) and behavioral emotional design (positive vs. neutral). The behavioral positive emotional design allows learners to interact with learning materials, whereas behavioral neutral emotional design only allows learners to watch learning video. Results showed that both visually attractive and behaviorally interactive design (visual positive emotion design and behavioral positive emotional design) had positive effect on learners’ positive emotions. Combining visual positive with behavioral positive emotional design could facilitate learning performance.